Analysis of the Calculation of Fixed Assets Depreciation Methods Between PSAK and the Taxation Law and Its Implications for Financial Statements (Case Study at Pt. Prima Beton Bangun Persada).: Analisis Perhitungan Metode Penyusutan Aktiva Tetap Antara PSAK Dan UU Perpajakan Serta Implikasinya Terhadap Laporan Keuangan (Studi Kasus Pada Pt. Prima Beton Bangun Persada). - Yona Novia Nur Chumaidah; Imelda Dian Rahmawati (Academia Open, 2021)
In the face of a business world whose competition is getting tougher, a company is required to have a goal that will maintain the survival of the company, in achieving these goals, the company must be able to move the wheels of the company well, the goal of each company is to achieve optimal returns on the investment it invests. , while the investment is in the form of fixed assets. This study aims to determine the implications of the financial statements resulting from the existing depreciation method. The depreciation method used is the straight-line depreciation method, the double-declining balance depreciation method, and the total year depreciation method. The data used in this study are primary data, companies for the 2016 & 2017 financial reporting period. By using the straight-line depreciation method the implications in the Financial Statements, especially on the profit generated, experience and fluctuate or fluctuate packs that can go up or down, using the method double-declining balance depreciation the resulting profit experiences a fluctuating or variable impact, it can increase or decrease, and by using the depreciation method the number of years profit has a fluctuating impact but the depreciation value increases with this method the percentage difference is very large and cannot be used as a basis for determining cost of depreciation